2021
DOI: 10.21776/ub.habitat.2021.032.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Price Integration Analysis of Crude Oil and Vegetable Oils

Abstract: The importance of palm oil as Indonesia's main export commodity from the non-oil and gas sector makes a study about the price integration of crude oil and vegetable oils is conducted. The time-series data is used are monthly data from 2002:2 to 2019:4. Using the Vector Correction Model (VECM), this study aimed to analyze the price integration among Log of Crude Oil Price (LCOP), Palm Oil Price (LPOP), Soybean Oil Price (LSOP), Sun Flower Oil Price (LSFOP) and Rapeseed Oil Price (LROP). Augmented-Dickey Fuller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(18 reference statements)
0
4
0
1
Order By: Relevance
“…Among vegetable oils, the cross-price elasticities commonly represent a positive impact on the soybean oil markets, such that a 1% change in the prices of canola oil (0.59%), palm oil (0.34%), corn oil (0.14%), and sunflower oil (0.69%) would determine the price of soybean oil in the US markets in a positive relation. This was followed by a study conducted by Destiarni et al [58], who observed, among vegetable oils, that the price elasticity relationship has a strong substitution effect on determining the oil market demands.…”
Section: Long-term Relationship Impact On Indonesian Coconut Oil Exportsmentioning
confidence: 96%
“…Among vegetable oils, the cross-price elasticities commonly represent a positive impact on the soybean oil markets, such that a 1% change in the prices of canola oil (0.59%), palm oil (0.34%), corn oil (0.14%), and sunflower oil (0.69%) would determine the price of soybean oil in the US markets in a positive relation. This was followed by a study conducted by Destiarni et al [58], who observed, among vegetable oils, that the price elasticity relationship has a strong substitution effect on determining the oil market demands.…”
Section: Long-term Relationship Impact On Indonesian Coconut Oil Exportsmentioning
confidence: 96%
“…Vegetable oils are another food category that is analyzed in this research. Destiarni and Jamil (2021) investigate the relationship between crude oil and vegetable oils. The vegetable oils available in the study are palm oil, soybean oil, sun flower oil, and rapeseed oil.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Pada dasarnya integrasi pasar dapat didekati baik secara vertical maupun horizontal. Dari sisi alat analisis, terdapat beberapa alat analisis yang digunakan dalam menganalisis integrasi pasar seperti Vector Error Correction Model (Destiarni & Jamil 2021) dan Index of Market Connection (Agung & Daryanto, 2017). Analisis integrasi pasar digunakan untuk mengetahui keterpaduan harga melalui pendekatan secara vertikal dengan penggunaan alat analisis IMC.…”
Section: Metodeunclassified